PENGINTEGRASIAN MATERI ISLAM DI INDONESIA DENGAN HASIL KEBUDAYAAN ISLAM (GREBEG SURO DI JIPANG, CEPU, BLORA, JAWA TENGAH) - Fitriah Hanim; Sariyatun Sariyatun (Jurnal Pendidikan Sejarah Indonesia, 2020)
Social Science lessons that have been in the school curriculum only exemplify and discuss material globally or nationally. And students pay less attention and are less interested because the scope is not in their environment. From these problems, in the social studies curriculum it is necessary to add local historical material related to the local culture. Which in this case is the national material on Islamic material in Indonesia and its cultural results, the example of that culture can be exemplified is Grebeg Suro Jipang. It is expected that from studying this material, students know the benefits of learning to preserve and can benefit from learning, at least from the meaning of the grebeg, the attitude that can be learned is social attitudes such as mutual cooperation, cooperation, and sharing with others. Nor do spiritual attitudes like gratitude.